RELATIONSHIP BETWEEN BODY MASS INDEX AND LIPID PROFILE IN PATIENTS AT IBNU SINA HOSPITAL MAKASSAR. - Putri Handayani (Yayasan Pendidikan Medika Indonesia, 2026)
Background: Body Mass Index (BMI) is commonly used as an indicator of nutritional status to assess the risk of metabolic and cardiovascular diseases. Abnormal lipid profiles, including elevated total cholesterol, LDL, triglycerides, and reduced HDL levels, are known contributors to cardiovascular disease. However, the association between BMI and lipid profile may vary across populations. Objective: This study aimed to determine the relationship between Body Mass Index and lipid profile among patients at Ibnu Sina Hospital, Makassar, in 2024. Methods: This study employed an observational analytic design with a cross-sectional approach. Data were obtained from medical records of adult patients who underwent BMI and lipid profile examinations in 2024. A total of 83 patients were included using total sampling. The association between BMI and lipid profile was analyzed using the Chi-square test with a significance level of 0.05. Results: Most respondents had a normal BMI. The majority of patients showed normal total cholesterol and triglyceride levels, while low HDL and high LDL levels were still frequently observed. Chi-square analysis showed no significant association between BMI and total cholesterol (p=0.173), HDL (p=0.417), LDL (p=0.769), or triglycerides (p=0.677). Conclusion: There was no significant relationship between Body Mass Index and lipid profile among patients at Ibnu Sina Hospital, Makassar. Other factors beyond BMI may influence lipid profile abnormalities.